Derivation of weed intensity maps in wheat (Triticum aestivum) using spatial data with GIS in the central districts of Punjab, India - KAUR, RAMANJIT; MAHEY, R K; SOOD, ANIL (The Indian Journal of Agricultural Sciences, 2015)
Remote sensing technologies are playing an increasingly important role in agricultural production. Because of their potential for high spatial and spectral resolution, satellite and aircraft images can contain detailed site specific information about conditions in agricultural fields. It can be used for monitoring crop growth, yield potential, soil conditions, weed intensity etc. For the commercial extension of site-specific herbicide application technology, rapid and cost effective methods for creating accurate weed maps are required. An experiment was conducted to generate weed prescription maps using spatial data with GIS and remote sensing in the central districts of Punjab, India 2007-08 and 2008-2009. The objective of this research was to demonstrate the potential of optical airborne remote sensing in the detection of some specific weeds and their densities in wheat (Triticum aestivum L.) crop in the central districts of Punjab, India. The analysis of spectral and ground measurement was done to select wave bands (wavelength regions) suitable for distinguishing weed-infested and weed-free crop areas. The results of this study showed that weed prescription mapping can be used for forecasting the infestations, on the basis of which farmers can be take the preventive control measures for weed control, which ultimately helps them in preventing yield losses and these weed maps can also be used as an input in yield forecasting models in future.